THE USE OF ANIMATION MOVIE WITH TEXT IN IMPROVING STUDENTSâ€™ VOCABULARY FOR SPEAKING - Rahmani, Teresa Sari; Rufinus, Albert; Salam, Ura (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to identify extent the use of animation movie with text in teaching vocabulary for speaking. The population of the research was the eighth grade students of SMP N 2 Pontianak in the academic 2016/2017 which VIII D as the sample. The researcher conducted a pre-experimental. The research finding showed the total of the pre-test about vocabulary for speaking was 1975 with the mean score 53.37 and it was categorized as â€œPoor to Averageâ€. Furthermore, the total score of post-test was 2850 with the mean score 77.02 and it was categorized as â€œAverage to Goodâ€.Â Based on the data analysis, it was found that the effect size this research is 1.57, which categorized as â€œHigh Effectâ€. It can be concluded that the use of animation movie with text can improves the studentsâ€™ vocabulary for speaking significantly.Â Keyword: Animation Movie, Vocabulary, Speaking